ANALISIS PENGARUH PENDAPATAN, HARGA, PREFERENSI, DAN GAYA HIDUP TERHADAP PERILAKU KONSUMSI MAKANAN JEPANG (STUDI PADA MAHASISWA FEB UB) - Ramadhan, Muh. Rizki; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2024)
Today, students' consumption is not only limited to college-related needs but also extends to the desire for certain types of food, including Japanese cuisine. Japanese food has become one of the most popular international cuisines in Indonesia, as evident from the increasing number of Japanese food outlets across various cities in the country. The aim of this study was to determine the impact of income, price, preferences, and lifestyle on Japanese food consumption behavior among students of the Faculty of Economics and Business at Brawijaya University. Data collection techniques in this study involved distributing questionnaires to 100 students. Based on the results of binary logistic regression analysis, it shows that partially, income, price, and lifestyle have a positive and significant effect on Japanese food consumption behavior. Meanwhile, preference has no significant effect on Japanese food consumption behavior.